Community knowledge, attitudes and practices related to tick-borne relapsing fever in Dodoma Rural District, Central Tanzania - Kisinza, W.N; Talbert, A; Mutalemwa, P; McCall, P.J (Tanzania journal of health research, 2008)
Tick-borne Relapsing Fever (TBRF) is a vector-borne disease of humans which causes serious illness, primarily for children under five years old and pregnant women. Understanding people's knowledge, attitude and practices on the disease is important in designing appropriate interventions. This study was conducted to explore community knowledge, attitudes and practices regarding TBRF transmission and control to provide baseline data for the planned scaling up of intervention in Dodoma rural District in central Tanzania. A total of 198 heads of households were interviewed using a semi-structured questionnaire. Of these, 94.5% were aware of TBRF. Fever of unknown origin (69.5 %), body pain (8.5%), headache (8.5 %), chills (4.5 %) and vomiting (3.5%) were the most commonly mentioned symptoms. The domestic tick-infestation and tickbites was known to 82.8%. High domestic tick infestation reported to occur during dry season (85.4%). The majority believed that the disease spreads through tick-bites (85.9%). Regular plastering of house floors and walls was the most common method used by the community to control domestic tick infestation (96.5 %). Majority (84.3 %) of the respondents preferred public healthcare facilities for treatment. Only a small proportion (15.7 %) preferred using traditional medicines. Poor knowledge of the study subjects about the disease and its control underscores the need for health educational campaigns if any control and/or elimination programme is to succeed.